Sudden Paradoxical QT‐Interval Prolongation Exacerbating T‐Wave Alternans in a Patient with Type 3 Long QT Syndrome. Issue 3 (17th July 2014) - Takasugi, Nobuhiro; Goto, Hiroko; Kuwahara, Takashi; Verrier, Richard L.
<x xml:space="preserve">Abstract</x> We report a case with type 3 congenital long QT syndrome, who exhibited a sudden paradoxical QT‐interval prolongation during a progressive increase in heart rate, which exacerbated T‐wave alternans.